(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The overall aim of this investigation is to determine the characteristics of raw municipal wastewater and assess the performance of UASB reactors to treat municipal wastewater of Baniwaleed city. The results showed that UASB reactors operated at ambient temperatures were highly effective in the treatment of wastewater at influent COD concentration 629 mg/l COD at HRT from 24 to 6 hours with the specific methane yield obtained was around 0.32 l CH4/g COD removed. The COD removal efficiencies were high at 95 % and total suspended solid removal was around 95%. The UASB technology provides a low-cost system for the direct treatment of municipal wastewater.